Impact Of Enclosures On Range Productivity In Chepareria West Pokot County, Kenya - Waiganjo, Regina Wambui (My University, 2023)
In the semi-arid areas of West Pokot particularly Chepareria, the majority of the people live semi sedentary lives while others are nomadic pastoralists. In the last three decades, there have been concerted efforts to restore and improve rangeland in this area. Use of enclosures, which is one of the key interventions, by the Vi Agro- forestry a Non-Governmental Organisation, enhancing with many ecological processes such as disturbance, is a method of rehabilitating degraded rangeland, which in turn affects vegetation dynamics. Adoption of these strategies by farmers has been gradual and some areas are still open and degraded. The aim of this study was to evaluate the effects of enclosures on range productivity in the semi-arid rangeland in West Pokot. Plant productivity, diversity and density were assessed in enclosures of different ages and in adjacent open land used for communal grazing. Questionnaires were also used to assess local community perception of the range restoration and improvement. Modified Whittaker plot was used for sampling in the selected enclosures and open areas. Herbaceous biomass and plant cover were greater in enclosures than in open areas. The average herbaceous cover in the enclosed area was 76% while that in the open it was 55% which was significantly different, p<0.001. The average herbaceous biomass in the enclosure was 137.2kg/ha while in the open it was 37.8kg/ha respectively. Enclosed areas are more productive than open areas and should be adopted in other dry areas as a method of rehabilitating degraded grazing lands.
Keywords: Enclosurers; Range Productivity; West Pokot